Family Dysfunction, Parental Role Abdication and High Rate of Kidnapping among Young People in Enugu State, Nigeria. (Psychological Implications) (British Journal of Multidisciplinary and Advanced Studies, 2023)
The family is one of the most fundamental social unit of the society. It consists of group of individuals united by blood, marriage, adoption and other intimate ties. Being regarded as the foundation of every human being, any form of negative treatment, abnormality and confusion emanating from it poses a great threat and catastrophe to the young people and society at large. Therefore, this study sought to investigate family dysfunction, role abdication and high rate of kidnapping in Enugu State, Nigeria. Two purpose of study and hypotheses guided the study accordingly. The study was delimited to Enugu South local government area of Enugu State. Correlational survey design was used as well as a sample study of 300 young people purposively selected using accidental sampling. The instrument was researcher structured questionnaire adapted from The Questionnaire of Family Functioning (2008) and Dyadic Parent-Adolescent-Role confusion scale (DPARCS, 2018) face validated by three experts from Educational Psychology, Sociology and Measurement and Evaluation from Enugu State University of Science and Technology. Reliability co-efficient of 0.76 was determined using Cronbach Alpha. Data was collected with the help of two research assistant and hypotheses analyzed using Pearson Product Moment Correlation. Based on the findings, it was recommended amongst others, that families should rise up to its foundational task of unconditional love as well as assumption of its responsibilities to family members in order to groom youths that are well equipped emotionally and psychologically.